Coating optimization of yield pseudoplastic paste-based stereolithography 3D printing of alumina ceramic core. Issue 20 (15th October 2022) - Xing, Hongyu; Lai, Lei; Zhao, Yanhua; Liu, Jianhua; Yu, Hanwen; Zhang, Zhenzhong
Abstract: Yield pseudoplastic paste is prepared for self-supported stereolithography (SLA ) 3D printing with critical shear stress of 290.7 Pa and viscosity of 28810 mPa·s under strain rate of 30 s −1 . Simulation analysis of paste coating is carried out based on established constitutive equation. Furthermore, corresponding stress field is analyzed under different layer thicknesses (25–100 μm) and blade speeds (1.5–4.5 mm/s). Then, flexural strength, porosity, surface roughness and microstructure of components, printed with different layer thicknesses and sintered at different temperatures, are systematically investigated. Finally, complex-shaped cores are fabricated with flexural strength of 38.56±1.45 MPa, porosity of 21.57±0.8% and surface roughness of Ra  < 3 μm. The optimized parameters include layer thickness of 25–50 μm, blade speed of 3.5 mm/s, and sintering temperature of 1300 o C. Moreover, step-like undulating fracture morphology of the core is observed along printing layer, which shows that the coating process has an important influence on the mechanical properties of ceramic parts.